2007
DOI: 10.1044/1092-4388(2007/090)
|View full text |Cite
|
Sign up to set email alerts
|

Acquisition of English Grammatical Morphology by Native Mandarin-Speaking Children and Adolescents: Age-Related Differences

Abstract: Findings support an Environmental account for age-related differences in 2nd language (L2) morphological acquisition. Results also indicate that the acquisition of some grammatical morphemes by school-aged immigrants takes several years to complete. As L2 learners exhibit some error types and difficulties similar to monolingual children with specific language impairment, caution needs to be taken when interpreting and using morphological errors as indicators of speech/language learning problems in this populat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

20
172
3
3

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 157 publications
(209 citation statements)
references
References 31 publications
20
172
3
3
Order By: Relevance
“…Numerous studies have shown that child English L2 learners also display variable use of tense morphemes in their interlanguage (Dulay & Burt, 1973, 1974Gavruseva, 2002Gavruseva, , 2004Haznedar, 2001;Haznedar & Schwartz, 1997;Ionin & Wexler, 2002;Jia & Fuse, 2007;Lakshmanan, 1994;Paradis, 2005). The more particular question for our purposes is whether they show the (E)OI patterns as described above in their use of optional infinitives.…”
Section: Optional Infinitives and L2 Theoretical Accountsmentioning
confidence: 99%
“…Numerous studies have shown that child English L2 learners also display variable use of tense morphemes in their interlanguage (Dulay & Burt, 1973, 1974Gavruseva, 2002Gavruseva, , 2004Haznedar, 2001;Haznedar & Schwartz, 1997;Ionin & Wexler, 2002;Jia & Fuse, 2007;Lakshmanan, 1994;Paradis, 2005). The more particular question for our purposes is whether they show the (E)OI patterns as described above in their use of optional infinitives.…”
Section: Optional Infinitives and L2 Theoretical Accountsmentioning
confidence: 99%
“…In sum, all three language groups were similar in terms of proficiency but different regarding other characteristics. The differences, however, should not constitute a problem in this case given that they would, if anything, reduce the effect of interest -i.e., Italian-and Spanish-speaking participants (who are expected to produce more errors) have an advantage in English due to their speaking it considerably more frequently (Jia & Fuse, 2007); furthermore, Italian speakers had also been immersed in an English-speaking environment for longer periods. And, in any case, the marginal advantage of the younger acquisition age of the Dutch participants (no more than 6 years) is unlikely to have major effects on the results since it does not span the critical age (Johnson & Newport, 1989).…”
mentioning
confidence: 99%
“…(But see Jia & Fuse 2007, for evidence that older cL2 learners might take longer.) Golberg et al (2008) examined receptive vocabulary size in English L2 children over time and found that they nearly caught up to their native-speaker age peers in three years of exposure to English.…”
Section: Johanne Paradismentioning
confidence: 99%